2021
DOI: 10.3390/ijerph181910212
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Short Daytime Nap on the Cognitive Performance: A Systematic Review and Meta-Analysis

Abstract: Background: Napping in the workplace is under debate, with interesting results on work efficiency and well-being of workers. In this systematic review and meta-analysis, we aimed to assess the benefits of a short daytime nap on cognitive performance. Methods: PubMed, Cochrane Library, ScienceDirect and PsycInfo databases were searched until 19 August 2021. Cognitive performance in working-aged adults, both before and following a daytime nap or under control conditions (no nap), was analysed by time and by type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 81 publications
(289 reference statements)
0
13
0
Order By: Relevance
“…Even if we did not demonstrate that women were more at risk than male HCWs, women might be more at risk of PTSD [ 1 , 2 ], caused by the additional strain imposed because of their social roles [ 42 ]. Some studies showed that young adults may be at higher risk of PTSD [ 57 ]. Lack of experience [ 34 , 38 ] may be compensated by organizing teamwork between the older and younger HCWs [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even if we did not demonstrate that women were more at risk than male HCWs, women might be more at risk of PTSD [ 1 , 2 ], caused by the additional strain imposed because of their social roles [ 42 ]. Some studies showed that young adults may be at higher risk of PTSD [ 57 ]. Lack of experience [ 34 , 38 ] may be compensated by organizing teamwork between the older and younger HCWs [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that the ESS did not reliably predict moderate-to-severe OSA, in agreement with Miller and Ghandeharioun et al ( 10 , 24 ). Maybe it was because that the ESS is totally subjective and influenced by many factors including daytime naps and blood pressure ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Stress at work is a major public health concern. This is especially true among healthcare workers (HCWs) and even more concerning in the Emergency Departments (ED) due to shifting work, fatigue and lack of sleep [ 1 ], poor food intake [ 2 ], and life-threatening emergencies in the context of overcrowding and job demands [ 3 , 4 ]. Currently, the best scale to assess stress levels at work is the job-demand-control-support model (JDCS), a self-reported psychological questionnaire created and validated by Karasek in 1981 [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%